Research Challenges and Opportunities in Mobile Applications - Hakkani-Tür, Dilek; Tur, Gokhan; Heck, Larry (IEEE Signal Processing Magazine, 2011)
We have attempted to distill the research challenges and opportunities for mobile applications, ranging from personalization to connectivity. We believe that interactive multimodal mobile applications are still in their infancy and this is an exciting emerging field for research and development.